Skeletal malformations in Australian marine finfish hatcheries - Cobcroft, J M; Battaglene, S C (Aquaculture, 2013)
The Australian finfish aquaculture industry has a target to more than treble production from 2005 to 100,000 t p.a. by 2015. Most of the current production is from sea cage culture of Salmo salar and Thunnus maccoyii but new and emerging species are predicted to have a faster increase in production and were the focus of this study. The quantity and quality of hatchery-produced fingerlings is an impediment to achieving growth in the marine finfish sector. A survey of 18 hatcheries revealed that 44% indicated skeletal malformations were a significant issue in hatchery production, and 89% reported variability in malformation rates between production batches. Samples of fish from selected hatcheries were cleared and stained for assessment of abnormal bone development. Two hatcheries that had indicated malformations were not a significant problem submitted samples with > 5% severe malformations. Jaw and spinal malformations occurred in Lates calcarifer, Seriola lalandi, Epinephelus fuscoguttatus, E. coioides, and Latris lineata. To the best of our knowledge, causative factors of malformations in Australian hatcheries have only been identified for jaw malformation in Lates calcarifer and Latris lineata, and further research is either needed or underway with other species and malformation types in order to improve culture protocols and increase fingerling quality. Improved monitoring techniques for skeletal malformations would substantially enhance the comparison of production methods at a commercial scale and enhance research efforts.